Enzyme-Linked Electrochemical Detection of PCR-Amplified Nucleotide Sequences Using Disposable Screen-Printed Sensors. Applications in Gene Expression Monitoring - Horaková-Brazdilova, Petra; Fojtova, Miloslava; Vytras, Karel; Fojta, Miroslav (Sensors (Basel, Switzerland), 2008)
Electrochemical enzyme-linked techniques for sequence-specific DNA sensingare presented. These techniques are based on attachment of streptavidin-alkalinephosphatase conjugate to biotin tags tethered to DNA immobilized at the surface ofdisposable screen-printed carbon electrodes (SPCE), followed by production andelectrochemical determination of an electroactive indicator, 1-naphthol. Via hybridizationof SPCE surface-confined target DNAs with end-biotinylated probes, highly specificdiscrimination between complementary and non-complementary nucleotide sequences wasachieved. The enzyme-linked DNA hybridization assay has been successfully applied inanalysis of PCR-amplified real genomic DNA sequences, as well as in monitoring of planttissue-specific gene expression. In addition, we present an alternative approach involvingsequence-specific incorporation of biotin-labeled nucleotides into DNA by primerextension. Introduction of multiple biotin tags per probe primer resulted in considerableenhancement of the signal intensity and improvement of the specificity of detection.
Keywords: primer extension; electrochemical detection; DNA hybridization; enzyme-linked assay; gene expression; PCR